Hamiltanian minimum principle for optimum control of the distance learning process - S. Ya. Zhukovich (Системный анализ и прикладная информатика)
A mathematical learning model based on control theory in the form of an inhomogeneous linear differential equation is proposed. Analytical formulas and graphs for optimal program control and optimal trajectory are obtained from the principle of the minimum of the Hamiltonian for autonomous systems.